THE RELATIONSHIP OF MAN AND SOCIETY IN LEV TOLSTOY’S NOVEL “RESURRECTION” (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the relationship between the inner world of a person and society, their mutual influence, and the issue of moral criteria on the example of Lev Tolstoy’s novel “Resurrection”. “Resurrection” is one of the most important socio-philosophical works of the great Russian writer Lev Tolstoy, in which the complex relationship between man and society is deeply artistically interpreted. The life of Russia at the end of the 19th century, the judicial system in the country, problems such as social inequality and moral crisis are placed in the center of the novel. Through the work, the author revealed not only the process of spiritual awakening of a person, but also the influence of the social system on human destiny.
Keywords: Resurrection, Tolstoy, society, Nekhlyudov, Maslova, fate, court, social inequality.